2g-e=3g(g-e) make “g” the subject of the expression

Question

2g-e=3g(g-e) make “g” the subject of the expression

in progress 0
Raelynn 2 weeks 2021-09-10T14:27:15+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-10T14:29:11+00:00

    Answer:

    T=6/√(1+g^2) make g the subjectT=6/√(1+g^2) make g the subject

    Step-by-step explanation:

    T=6/√(1+g^2) make g the subjectT=6/√(1+g^2) make g the subjectT=6/√(1+g^2) make g the subjectT=6/√(1+g^2) make g the subjectT=6/√(1+g^2) make g the subject

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )